Mechanism of protecting forest and land resources of ukraine from illegal amber mining: legal aspect - Bulgakov, A. O.; Ivantsov, V. O.; Іванцов, В. О.; ORCID: http://orcid.org/0000-0002-2904-0466; Makarenko, V. S.; Макаренко, В. C.; ORCID: http://orcid.org/0000-0003-3310-0684; Dubova, K. O.; Klimova, S. M. (Naukovyi Visnyk Natsionalnoho Hirnychoho Universytetu. – 2022. - № 1. – Р. 83-87, 2022)
Встановлено, що під кримінально-правову охорону ст. 240-1 КК України підпадають суспільні відносини щодо охорони й раціонального використання ресурсів бурштину, лісових і земельних ресурсів. При цьому перші становлять основний безпосередній об’єкт злочину, другі – є безпосередніми додатковими об’єк тами цього злочину. Встановлено коло предметів цього злочину – бурштин, лісові та земельні ресурси. Встановлено конкуренцію норм ст. ст. 240-1 і 245 і ст. ст. 240-1 та 239 КК України

It is established that the object of the crime under Article 240-1 of the Criminal Code includes the main direct object – public relations for the protection and rational use of amber resources and two direct additional objects of crime: public relations for the protection and rational use of forest and land resources. It is determined that damage to forests due to illegal amber mining must be further qualified under Part 1 of Article 245 of the Criminal Code of Ukraine if illegal mining is carried out in a generally dangerous manner. This crime must be further qualified under Part 1 of Article 239 of the Criminal code of Ukraine if illegal extraction of amber is carried out with violation of special rules of treatment of substances, waste or other materials.

Установлено, что под уголовно-правовую охрану ст. 240-1 УК Украины подпадают общественные отношения по охране и рациональному использованию ресурсов янтаря, лесных и земельных ресурсов. При этом первые составляют основной непосредственный объект преступления, вторые – являются непосредственными дополнительными объектами этого преступления. Установлен круг предметов этого преступления – янтарь, лесные и земельные ресурсы. Установлена конкуренция норм ст. ст. 240-1 и 245 и ст. ст. 240-1 и 239 УК Украины
Mechanism of protecting forest and land resources of ukraine from illegal amber mining: legal aspect / A. O. Bulgakov, V. O. Ivantsov, V. S. Makarenko, K. O. Dubova, S. M. Klimova // Naukovyi Visnyk Natsionalnoho Hirnychoho Universytetu. – 2022. - № 1. – Р. 83-87. – DOI: https://doi.org/10.33271/nvngu/2022-1/083
Keywords: охорона надр України; незаконний видобуток бурштину; охорона лісів і земель; кримінальна відповідальність; protection of subsoil of Ukraine; illegal amber mining; protection of forests and lands; criminal liability; охрана недр Украины; незаконная добыча янтаря; охрана лесов и земель; уголовная ответственность; publikatsii u Scopus; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; Земельне право. Аграрне право. Land Law. Agrarian Law. Земельное право. Аграрное право